Hearing loss configurations in low- and middle-income countries - Newall, John; Kim, Rebecca; Dawes, Piers; Ismail, Afzarini Hasnita (Taylor & Francis, 2025)
Objective: The majority of individuals with hearing loss worldwide reside in low‑ and middle‑income countries (LMICs), but there is limited information regarding the characteristics of hearing loss in these regions. This descriptive study aims to address this knowledge gap by analysing audiogram patterns in LMIC populations. Greater knowledge about the properties of hearing loss in LMICs allows for improved planning of interventions. Study sample: Retrospective data from 23 collaborating centres across 16 LMICs were collected. All participants were adults seeking help for hearing problems. A machine learning approach was utilised to classify the hearing threshold data and identify representative profiles. The study comprised 5773 participants. Results: The results revealed mildly sloping audiometric patterns with varying severity. The patterns differed from previous studies conducted in high‑income regions, which included more steeply sloping losses. The findings also indicated a higher proportion of more severe levels of hearing loss. Conclusions: These variations could be attributed to population‑level differences in the causative mechanisms of hearing loss in LMICs, such as a higher prevalence of infectious disease‑related hearing loss. The results may also reflect differences in health‑seeking behaviours. This study highlights the need for tailored, scalable hearing interventions for LMICs.